Oral health strategy for the older people in social protection centers in Villavicencio, Colombia (2017)
Purpose - To design and to implement an oral health educational strategy that targeted an older population residing in three Social Protection Centers (SPC) in Villavicencio, Colombia. Design/methodology/approach - The first phase consisted in determining the oral health of older citizens in the SPC. To do this, the research group gathered patients’ personal information and indices. The second phase consisted in the development of an educational strategy based on the population’s requirements. The educational strategy, focusing on oral hygiene and denture care, was implemented for the older people and their caregivers. The third and final phase consisted in the research group measuring the effect of the designed strategy by repeating oral diagnoses for the older people six months after strategy implementation. Findings - The results of the assessment indicated that implementing a strategy to strengthen oral hygiene care was positive, given that statistically significant reductions were observed in the Soft Plaque Index and the Gingival Index (p<0.05). Research limitations/implications - As a result of the complexity of the population, the data obtained after the strategy was implemented were significantly reduced. However, these results indicate that an educational strategy can have an effect on this type of population. Originality/value - Implementing a strategy that promotes oral hygiene education and brushing skills, fosters good oral behavior and helps the older people in SPC to remember the information taught, thus contributing to their oral hygiene.